Impacts of Denial-of-Service Attack on Energy Efficiency Pulse Coupled Oscillator (Baghdad Science Journal, 2023)
The Pulse Coupled Oscillator (PCO) has attracted substantial attention and widely used in wireless sensor networks (WSNs), where it utilizes firefly synchronization to attract mating partners, similar to artificial occurrences that mimic natural phenomena. However, the PCO model might not be applicable for simultaneous transmission and data reception because of energy constraints. Thus, an energy-efficient pulse coupled oscillator (EEPCO) has been proposed, which employs the self-organizing method by combining biologically and non-biologically inspired network systems and has proven to reduce the transmission delay and energy consumption of sensor nodes. However, the EEPCO method has only been experimented in attack-free networks without considering the security elements which may cause malfunctioning and cyber-attacks. This study extended the experiments by testing the method in the presence of denial-of-service (DoS) attacks to investigate the efficiency of EEPCO in attack-based networks. The result shows EEPCO has poor performance in the presence of DoS attacks in terms of data gathering and energy efficiency, which then concludes that the EEPCO is vulnerable in attack-based networks.